Airflow obstruction and small airway dysfunction following pulmonary tuberculosis: a cross-sectional survey - Xing, Zhenzhen; Sun, Tieying; Janssens, Jean-Paul; Chai, Di; Liu, Weiming; Tong, Yaqi; Wang, Yuxia; Ma, Yali; Pan, Mingming; Cui, Jia; Wang, Chen; Guo, YanFei (Thorax, 2023)
ObjectivesPulmonary function impairment and chronic respiratory symptoms after tuberculosis are relatively common in low-income and middle-income countries. We aimed to estimate the impact of post-tuberculosis (post-TB) on pulmonary function.MethodsThis large cross-sectional, population-based study included subjects aged 15 years or older with technically acceptable postbronchodilator spirometry measurements. Post-TB was diagnosed on the basis of radiological evidence and/or medical history. Airflow obstruction was defined as a postbronchodilator forced expiratory volume in 1 s/forced vital capacity ratio below the lower limit of normal of Global Lung Function Initiative (GLI) lung function equations. Small airway dysfunction was diagnosed if at least two of the following indicators were less than 65% of predicted: maximal mid-expiratory flow, forced expiratory flow (FEF) 50% or FEF 75%.ResultsIn this population sample (N=8680, mean age: 40.1 years), 610 (7.0% (95% CI 6.5 to 7.6) participants were post-TB. Post-TB subjects had more frequent respiratory symptoms (46.8% vs 28.3%). Among post-TB subjects, 130 (21.3% (95% CI 18.1 to 24.8)) had airflow obstruction; OR of airflow obstruction was significantly associated with post-TB after adjustment for other confounding factors (OR 1.31, 95% CI 1.05 to 1.62). Post-TB was also associated with small airway dysfunction (OR 1.28, 95% CI1.07 to 1.53), which was present in 297 (48.9% (95% CI 33.9 to 53.0)) post-TB subjects.ConclusionsOur findings support existing knowledge that post-TB is positively associated with pulmonary function impairment and make for frequent respiratory symptoms. Post-TB should be considered as a potentially important cause of airflow obstruction and respiratory symptoms in patients originating from countries with a high burden of tuberculosis.